The impact of Beauveria species bioinocula on the soil microbial community structure in organic strawberry plantations - Canfora, Loredana; Tartanus, Małgorzata; Manfredini, Andrea; Tkaczuk, Cezary; Majchrowska-Safaryan, Anna; Malusà, Eligio (Frontiers in Microbiology, 2023)
The multifunctionality of microorganisms, including entomopathogenic fungi, represents a feature that could be exploited to support the development, marketing and application of microbial-based products for plant protection. However, it is likely that this feature could affect the composition and dynamics of the resident soil microorganisms, possibly over a long period. Therefore, the methodology utilized to evaluate such impact is critical for a reliable assessment. The present study was performed to evaluate the impact of strains of Beauveria brongniartii and Beauveria bassiana on soil bacterial and fungal communities using an approach based on Terminal-Restriction Fragment Polymorphism (T-RFLP) analysis. Soil samples in the vicinity of the root system were collected during a 3-year period, before and after the bioinocula application, in two organic strawberry plantations. Specific primers were used for the amplification of the bacterial 16S rRNA gene and the fungal ITS region of the ribosome. Data of the profile analysis from T-RFLP analysis were used to compare OTUs occurrence and intensity in the inoculated soil with the uninoculated control. With regard to the impact on the bacterial community, both Beauveria species were not fully consistently affecting its composition across the seasons and fields tested. Nevertheless, some common patterns were pointed out in each field and, sometimes, also among them when considering the time elapsed from the bio-inoculum application. The impact was even more inconsistent when analysing the fungal community. It is thus concluded that the application of the bioinocula induced only a transient and limited effect on the soil microbial community, even though some changes in the structure dynamic and frequency of soil bacterial and fungal OTUs emerged.